2019
DOI: 10.1016/j.bbi.2019.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous activation of tumor necrosis factor receptor 2 promotes recovery from sensory and motor disease in a model of multiple sclerosis

Abstract: Tumor necrosis factor receptor 2 (TNFR2) is a transmembrane receptor that promotes immune modulation and tissue regeneration and is recognized as a potential therapeutic target for multiple sclerosis (MS). However, TNFR2 also contributes to T effector cell function and macrophage-TNFR2 recently was shown to promote disease development in the experimental autoimmune encephalomyelitis (EAE) model of MS. We here demonstrate that systemic administration of a TNFR2 agonist alleviates peripheral and central inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…In particular, it was shown that the expression level of TNFR2 is correlated to the suppressive potential of natural Tregs (nTregs) (Chen et al, 2007(Chen et al, , 2008(Chen et al, , 2010b, indicating that the most potent suppressors are highly susceptible to TNFR2 activation. It is well recognized now that TNFR2 contributes to the expansion of CD4 + FoxP3 + nTregs in vitro and in vivo (Chen et al, 2007(Chen et al, , 2008Okubo et al, 2013;Chopra et al, 2016;Fischer et al, 2017Fischer et al, , 2018Fischer et al, , 2019aPadutsch et al, 2019) and the stabilization of the CD4 + Foxp3 + Treg phenotype in the inflammatory environment (Chen et al, 2013). Like CD4 + Tregs, CD8 + suppressor cells can express FoxP3 and CD25.…”
Section: Inflammatory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it was shown that the expression level of TNFR2 is correlated to the suppressive potential of natural Tregs (nTregs) (Chen et al, 2007(Chen et al, , 2008(Chen et al, , 2010b, indicating that the most potent suppressors are highly susceptible to TNFR2 activation. It is well recognized now that TNFR2 contributes to the expansion of CD4 + FoxP3 + nTregs in vitro and in vivo (Chen et al, 2007(Chen et al, , 2008Okubo et al, 2013;Chopra et al, 2016;Fischer et al, 2017Fischer et al, , 2018Fischer et al, , 2019aPadutsch et al, 2019) and the stabilization of the CD4 + Foxp3 + Treg phenotype in the inflammatory environment (Chen et al, 2013). Like CD4 + Tregs, CD8 + suppressor cells can express FoxP3 and CD25.…”
Section: Inflammatory Diseasesmentioning
confidence: 99%
“…Therefore, TNFR2 agonists were evaluated in models of inflammation and neurodegeneration (Table 3). Indeed, several articles using different TNFR2 agonists demonstrated that TNFR2 activation results in expansion of Tregs ex vivo and in vivo (Okubo et al, 2013;Chopra et al, 2016;Fischer et al, 2017Fischer et al, , 2018Fischer et al, , 2019a. Using the mouse TNFR2 agonist STAR2, Chopra et al (2016) showed that exogenous TNFR2 activation protected from acute graft-versus-host disease (GvHD) after allogeneic hematopoietic stem cell transplantation (allo-HCT) via host Treg cell expansion.…”
Section: Selective Activation Of Tnfr2 Using Agonistic Tnf Muteins Anmentioning
confidence: 99%
“…Treatment with solTNFR:Fc/p80 fusion protein reduced the clinical deficit of the first attack of relapsing-remitting EAE and decreased chemokine expression [ 134 ]. Moreover, activation of TNFR2 using antibody EHD2-sc-mTNFR2 in EAE mice delayed the day of onset of motor deficits and the development of motor disease and prevented weight loss after motor symptom onset [ 135 ]. These potential therapeutic effects of TNFR2 were associated to promotion of Treg activity and stability in the inflammatory environment: the resulting expansion of regulatory T cells reduced demyelination by promoting OPC proliferation [ 135 ].…”
Section: Evidence For Tnf Involvement In Pathological Hallmarks Ofmentioning
confidence: 99%
“…Accordingly, selective blockade of solTNF by genetic ablation or treatment with the soluble inhibitor XPro1595 resulted in disease amelioration in experimental models of MS [ 158 , 170 ] and ischemic stroke [ 171 , 172 ]. Another intriguing approach is represented by the use of selective TNFR2 agonists, which showed neuroprotective effects in a model of NMDA-induced acute neurodegeneration [ 173 ] and ameliorated motor and cognitive symptoms in EAE mice by simultaneously suppressing CNS autoimmunity and promoting remyelination [ 174 ].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%